Foreign Intervention in Africa after the Cold War Sovereignty, Responsibility, and the War on Terror - Schmidt, Elizabeth (Ohio University Press, 2018)
Poverty, corruption, and conflictsa ffect many parts of Africa, but the source of these problems is widely misunderstood. Many challenges today are rooted in colonial political and economic practices, Cold War alliances, and attempts by outsiders to influence political and economic systems during the decolonization and postindependence periods. This book provides a new framework for foreign political and military intervention in Africa, its purposes. It focuses on the 25 years following the Cold War, when neighboring states and subregional, regional, and global organizations and networks joined extracontinental powers in support of diverse forces in the war-making and peace-building processes. Two rationales were used to justify intervention: a response to instability (and the responsibility to protect) and the war on terror. Intended for nonpecialists, the book offers a new continentwide perspective, illuminated by case studies synthesized from previously published works.